Challenges and Opportunities in Research Methodologies for Contemporary Islamic Education Studies - Nahdliana 'Aisyatul 'Asyiroh; Firman Jumbati; Isnaini Isnaini; Langgeng Budianto (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This article examines the challenges and opportunities of research methodology in contemporary Islamic education studies. The rapid development of science, digital technology, and social transformation has encouraged significant changes in research approaches used to study Islamic education. This study aims to analyze the development of research methodologies, identify methodological challenges and opportunities, and explain their implications for the future of Islamic education studies. The research employed a qualitative approach using the library research method. Data were collected from scientific journal articles, books, proceedings, and other relevant academic sources, then analyzed through content analysis techniques. The findings indicate that research methodology in Islamic education has shifted from predominantly normative and textual approaches toward more empirical, contextual, interdisciplinary, and technology-based approaches. The study also reveals several challenges, including the integration of Islamic normative values with scientific objectivity, the complexity of educational issues, and ethical concerns in digital research. On the other hand, the development of mixed methods, digital technology utilization, interdisciplinary collaboration, and the integration of Islamic epistemology with modern scientific methodologies provide significant opportunities for strengthening Islamic education research. These developments have implications for improving methodological competence, digital literacy, curriculum reform, and the development of an integrative research paradigm. Therefore, adaptive and innovative methodological development is essential to enhance the quality, relevance, and contribution of Islamic education studies in responding to contemporary educational challenges.